Immunohistochemical analysis of sex hormone receptors in squamous changes of the urothelium. - Seitz, Julia; Hoegel, Josef; Eckstein, Markus; Lieb, Verena; Wullich, Bernd; Hartmann, Arndt; Rieker, Ralf (International Journal of Clinical and Experimental Pathology, 2022)
OBJECTIVE: Squamous cell transformation of the urinary bladder urothelium has various causes, symptoms, and few treatment options. The aim of this study was to analyze and compare the expression of sex hormone receptors in non-keratinized and keratinized squamous metaplasia (NKSM, KSM), squamous cell carcinoma (SCC), and healthy urothelium with regard to possible therapeutic approaches. METHODS: Biopsies from 26 patients with urothelial NKSM, KSM, and SCC were analyzed retrospectively. Tissue microarrays (TMA) of formalin-fixed paraffin-embedded (FFPE) bladder biopsies were stained with hematoxylin and eosin followed by immunohistochemical analysis with specific antibodies against estrogen, progesterone, and androgen receptors (ER, PR, AR) and assessment using the immunoreactive score. Statistical evaluations included the Wilcoxon signed-rank test and the Wilcoxon rank-sum test in the form of permutation tests. RESULTS: Of the 15 women and 11 men included in this explorative study, 17 had metaplasia: 15 (six men, nine women) had NKSM and two KSM (both men). A total of nine patients (three men, six women) had keratinized SCC or urothelial carcinoma with squamous differentiation. The comparison between normal urothelial cells and metaplasia showed a significantly stronger expression in the metaplastic tissue (P=0.0374). The invasive carcinoma showed significantly less PR than the extracellular matrix of the healthy urothelium (P=0.0026). Expression of AR was nearly absent in healthy and metaplastic urothelium. CONCLUSION: There appears to be an association between squamous metaplasia of the bladder mucosa and sex steroid hormone receptor expression, especially estrogen receptors. Topical hormone therapy should be considered.
EVALuna2:512116